Release from life, release in life : Indian perspectives on individual liberation - Bigger, Andreas; Krajnc, Rita; Metens, Annemarie; Schüpbach, Markus; Wessler, Hans Werner (Worlds of south and inner Asia ;, 2010)
"Festschrift u čast Peteru Schreineru"